IMPROVING STUDENTS’ SPEAKING SKILL USING INFORMATION GAP AT SECOND YEAR OF SMP N I NGRAMPAL SRAGEN IN 2010/2011 ACADEMIC YEAR - HANDAYANI , DWI (2011)
This research aims at knowing (1) the implementation of Information Gap technique in teaching speaking, and (2) describing the students’ response on Information Gap technique in teaching speaking. This research was implemented in SMP N I Ngrampal Sragen at the second year